Industrial gentrification in West Chelsea, New York: Who survived and who did not? Empirical evidence from discrete-time survival analysis. (January 2015) - Yoon, Heeyeun; Currid-Halkett, Elizabeth
This paper empirically tests the extent to which economic restructuring and gentrification affect viability and vulnerability businesses, with specific focus on arts and cultural industries in West Chelsea from 2000 through 2012. Based on the theoretical framework, gentrification stage model and adopting discrete-time survival analysis, we separately compare the risks of opening and closing between businesses established before/early stage of revitalisation (early-arrivers) and those established in the later stage (late-arrivers) within West Chelsea, versus their counterparts in the remainder of the study area in New York. We find that West Chelsea has been an advantageous location overall for late-arrivers in surviving in their market, while the early-arrived gallery and individual artists' enterprises have faced a higher risk of their operations closing. On the other hand, a higher proportion of new gallery and arts and cultural industries remain attracted to West Chelsea after 2000, suggesting that firms in those industries may be benefiting from the agglomeration effects and localisation economies associated with colocation. The higher opening probability of lodging venues (e.g. hotels) and other amenities signals an overall transformation of the neighbourhood and influx of new uses (and visitors) observed during this time frame.